Surveying the HPGe Gamma detector absolute efficiency - Tran, Tri Vien (H. : ĐHQGHN, 2017)
In many nuclear experiments, the energy efficiency of detector is a parameter without negligibility. In this paper, the absolute efficiency of HPGe detector is surveyed and mearsured at different distances from detector and different gamma energies.